Development of Economic Traits in Backcross Hybrids of Cotton Genetic Collection Lines - Khayitova Shakhlo Davlatovna (Genius Journals, 2022)
In the article, the research conducted in the lines of the cotton genetic collection of the National University of Uzbekistan is of particular importance. Development of economic traits in the cross-hybrids of the cotton genetic collection of the National University of Uzbekistan was determined experimentally.
Keywords: backcross hybrids; genetic collection; line; isogenic